Kardiales Troponin und mehr beim akuten Koronarsyndrom - Vafaie, Mehrshad; Stoyanov, Kiril M.; Katus, Hugo; Giannitsis, Evangelos (Der Internist, 2019)
Cardiac biomarkers are an integral component of the diagnostic work-up of patients with suspected acute coronary syndrome (ACS). Cardiac troponin (cTn) is the most sensitive diagnostic biomarker for patients with ACS and enables the differentiation of acute non-ST-elevation myocardial infarction (NSTEMI) from unstable angina. All cardiac and non-cardiac differential diagnoses must be taken into consideration. The use of cTn has a prognostic value in a multitude of acute and chronic diseases apart from ACS. Highly sensitive cTn (hsTn) assays should be preferentially used. Point-of-care (POC) troponin assays can be used for rule-in of acute MI but are generally not useful for rule-out of MI due to their lack of sensitivity compared to hsTn assays. This, however, may change with recent developments of newer and improved POC troponin assays. For exclusion of MI using hsTn assays, there are various protocols available, such as the instant rule-out with undetectable hsTn levels at admission or normal hsTn/cTn levels combined with normal copeptin levels or rule-out with serial controls of hsTn after 1, 2 or 3 h. This article provides an overview of guideline-recommended rule-out protocols for patients with suspected ACS and discusses recent advances in POC troponin assays.
Gesehen am 25.06.2019